Locally Anchored Disaster Mitigation Curriculum for Early Childhood Social Studies Learning: A Conceptual-Design Synthesis - Mulianingsih, Ferani; Purnomo, Arif; Riyani, Mufti; Astuti, Andarweni; Edi Siswanto, M. Bambang; Fajar, Fajar; Mapa, Mohammad Tahir; Aizawa, Yosio (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – Disaster mitigation education for young children is often reduced to drills, hazard information, and safety procedures. This conceptual article formulates LADMiC-ECE as a local wisdom-based disaster mitigation curriculum framework for Early Childhood Social Studies, positioning mitigation as social learning that develops place awareness, care, environmental responsibility, shared rules, and safe participation.Design/methods/approach – The article uses conceptual-design synthesis across five source clusters: Early Childhood Social Studies, disaster risk reduction education, local and Indigenous knowledge, play-based developmental learning, and authentic assessment with sustainability education. The sources were analysed to clarify theoretical hierarchy, identify novelty and resistance, and construct a developmental pathway.Findings – LADMiC-ECE is organised through five principles: place before hazard, culture before procedure, play before instruction, values before compliance, and observation before testing. Local wisdom is treated as cultural mediation of risk, not decoration or a substitute for scientific safety standards. The developmental pathway is recursive and context-sensitive, moderated by age, disability, trauma exposure, teacher capacity, family support, school resources, and hazard type.Research implications/limitations – The framework offers a conceptual basis for curriculum development, expert validation, teacher-community co-design, and child-centred assessment research. Its limitation is that it remains untested; it does not report classroom implementation, expert review, child observation, assessment reliability, or evidence of effectiveness across different hazards and communities.Practical implications – Teachers can adapt local stories, songs, maps, role play, guided walks, environmental routines, and observation records to connect safety with children’s familiar places and community life. Implementation must avoid frightening simulations, cultural romanticism, exclusionary practices, and transferring adult disaster responsibility to children.Originality/value – This article positions disaster mitigation within Early Childhood Social Studies rather than adult-oriented preparedness. Its novelty lies in integrating place, culture, play, and values into a developmentally appropriate curriculum that promotes socio-ecological awareness and mitigation behaviour.Paper type Conceptual paper